2010
DOI: 10.1007/s11274-010-0346-2
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory production and characterization of a new biosurfactant from Candida glabrata UCP1002 cultivated in vegetable fat waste applied to the removal of hydrophobic contaminant

Abstract: Biosurfactant production by Candida glabrata was studied using vegetable fat waste as substrate. A factorial design was initially carried out to investigate the effects and interactions of waste, yeast extract and glucose on the surface tension after 144 h cultivation. Maximum surface tension reduction was achieved with vegetable fat waste at 5% and yeast extract at 0.2%. The biosurfactant containing cell-free broth retained its surface-active properties after incubation at high temperatures, at a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The literature describes a number of waste products employed in biosurfactant production, such as vegetable oils, oily effluents [ 42 , 72 , 73 ], starchy effluents [ 74 , 75 ], animal fat [ 51 , 76 , 77 , 78 ], vegetable fat [ 79 ], vegetable cooking oil waste [ 72 , 80 , 81 , 82 ], soapstock [ 76 , 83 , 84 ] molasses [ 85 , 86 , 87 , 88 ], dairy industry waste (whey) [ 89 ], corn steep liquor [ 43 , 71 , 90 , 91 , 92 ], cassava flour wastewater [ 93 ], oil distillery waste [ 43 , 90 , 94 , 95 ] and glycerol [ 61 ]. Some of the most commonly employed industrial waste products for biosurfactant production are detailed below.…”
Section: Raw Materials For Biosurfactant Productionmentioning
confidence: 99%
“…The literature describes a number of waste products employed in biosurfactant production, such as vegetable oils, oily effluents [ 42 , 72 , 73 ], starchy effluents [ 74 , 75 ], animal fat [ 51 , 76 , 77 , 78 ], vegetable fat [ 79 ], vegetable cooking oil waste [ 72 , 80 , 81 , 82 ], soapstock [ 76 , 83 , 84 ] molasses [ 85 , 86 , 87 , 88 ], dairy industry waste (whey) [ 89 ], corn steep liquor [ 43 , 71 , 90 , 91 , 92 ], cassava flour wastewater [ 93 ], oil distillery waste [ 43 , 90 , 94 , 95 ] and glycerol [ 61 ]. Some of the most commonly employed industrial waste products for biosurfactant production are detailed below.…”
Section: Raw Materials For Biosurfactant Productionmentioning
confidence: 99%
“…Given the industrial importance of yeasts and their potential to biosurfactant production, a growing number of aspects related to the production of biosurfactants from yeasts have been the topic of research during the last decade (Amaral et al, 2010). Some species of Candida , such as Candida bombicola (Roelants et al, 2013; Luna et al, 2016), Candida glabrata (Luna et al, 2009; Gusmão et al, 2010), Candida lipolytica (Santos et al, 2013; Rufino et al, 2014), Candida sphaerica (Sobrinho et al, 2013a; Luna et al, 2015), Candida utilis (Campos et al, 2013), Candida guilliermondii (Sitohy et al, 2010), Candida antarctica (Kim et al, 2002; Hua et al, 2003), and Candida tropicalis (Batista et al, 2010; Priji et al, 2013) are known to produce biosurfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial wastes have attracted considerable interest from researchers as low-cost substrates for this purpose, as the substrate generally accounts for up to 50% of the final production cost (Das et al, 2009; Rufino et al, 2014). Residues, such as corn steep liquor (Silva et al, 2013), glycerol (Silva et al, 2010), clarified cashew apple juice (Oliveira and Garcia-Cruz, 2013), vinasse (Oliveira et al, 2013), cassava wastewater (Barros et al, 2008), soybean oil refinery residue (Luna et al, 2011a), ground-nut oil refinery residue (Sobrinho et al, 2008), animal fat (Santos et al, 2013), vegetable fat (Gusmão et al, 2010), waste frying oil (Batista et al, 2010), and molasses (Santos et al, 2010) have demonstrated excellent results when used for biosurfactant production by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…80,81 Low-cost media based on animal fat and CSL combined with glucose, yeast extract, urea, and other inorganic nitrogen sources were evaluated for the production of biosurfactants by the yeast Candida lipolytica. (82) Only 2.5% of the CSL remained after six days and 2.2 g/L of crude biosurfactant was produced, causing a maximum reduction in surface tension from 50 to 28 mN/m.…”
Section: Cereal Biorefinery Waste Valorizationmentioning
confidence: 99%